Impact of SULT1A3/SULT1A4 genetic polymorphisms on the sulfation of phenylephrine and salbutamol by human SULT1A3 allozymes. Issue 5 (July 2019) - Bairam, Ahsan F.; Rasool, Mohammed I.; Alherz, Fatemah A.; Abunnaja, Maryam S.; El Daibani, Amal A.; Gohal, Saud A.; Alatwi, Eid S.; Kurogi, Katsuhisa; Liu, Ming-Cheh
Abstract : Objectives: Phenylephrine and salbutamol are drugs that are used widely to treat diseases/disorders, such as nasal congestion, hypotension, and asthma, in individuals of different age groups. Human cytosolic sulfotransferase (SULT) SULT1A3 has been shown to be critically involved in the metabolism of these therapeutic agents. This study was carried out to investigate the effects of single nucleotide polymorphisms of human SULT1A3 and SULT1A4 genes on the sulfation of phenylephrine and salbutamol by SULT1A3 allozymes. Materials and methods: Wild-type and SULT1A3 allozymes, prepared previously by site-directed mutagenesis in conjunction with bacterial expression and affinity purification, were analyzed for sulfating activity using an established assay procedure. Results: Purified SULT1A3 allozymes, in comparison with the wild-type enzyme, showed differential sulfating activities toward phenylephrine and salbutamol. Kinetic studies showed further significant variations in their substrate-binding affinity and catalytic activity toward phenylephrine and salbutamol. Conclusion: The results obtained showed clearly the differential enzymatic characteristics of SULT1A3 allozymes in mediating the sulfation of phenylephrine and salbutamol. This information may contribute toward a better understanding of the pharmacokinetics of these two drugs in individuals with distinct SULT1A3 and/or SULT1A4 genotypes.